Ultrasound-Guided Multiple Peripheral Nerve Blocks in a Superobese Patient - Alper Kilicaslan; Ahmet Topal; Atilla Erol; Hale Borazan; Onur Bilge; Seref Otelcioglu (Case Reports in Anesthesiology)
The number of obese patients has increased dramatically worldwide. Morbid obesity is associated with an increased incidence of medical comorbidities and restricts the application choices in anesthesiology. We report a successfully performed combined ultrasound-guided blockade of the femoral, tibial, and common peroneal nerve in a superobese patient. We present a case report of a 31-year-old, ASA-PS II, super obese man (190 kg, 180 cm, BMI: 58 kg/m2) admitted to the emergency department with a type II segmental tibia shaft fracture and ankle dislocation after a vehicle accident. After two failed spinal anesthesia attempts, we decided to apply a femoral block combined with a sciatic block. Femoral blocks were successfully performed with US guided in-plane technique. Separate blocks of the tibial and common peroneal nerves were planned after the sciatic nerve could not be located due to the thick subcutaneous tissue. We performed a tibial nerve block at 2 cm above the popliteal crease and common peroneal nerve at the level of the fibular head with US guided in-plane technique. The blocks were successful and no block-related complications were noted. Ultrasound guidance allows new approaches for multiple peripheral nerve blocks with low local anesthetic doses in obese patients.